N-[3,5-Bis(trifluoromethyl)phenyl]-5-bromo-2-hydroxybenzamide Analogues: Novel Acetyl- and Butyrylcholinesterase inhibitors - Kratky, Martin; Jaklova, Karolina; Štěpánková, Šárka; Svrčková, Katarína; Pflegr, Vaclav; Vinsova, Jarmila (Bentham Science Publishers Ltd., 2020)
Background: Development of acetyl- (AChE) and butyrylcholinesterase (BuChE) inhibitors belongs to viable strategies for the treatment of dementia and other diseases related to decrease in cholinergic neurotransmission. Objective: That is why we designed twenty-two analogues of a dual AChE-BuChE salicylanilide inhibitor, N[3,5-bis(trifluoromethyl)phenyl]-5-bromo-2-hydroxybenzamide 1, to improve its potency. Methods: We prepared N,N-disubstituted (thio)carbamates via direct acylation with (thio)carbamoyl chloride, N-n-alkyl monosubstituted carbamates using isocyanates as well as its salicylanilide core analogues. The derivatives were evaluated in vitro against AChE from electric eel and BuChE from equine serum using spectrophotometric Ellman's method. Results: The compounds showed moderate inhibition of both AChE and BuChE with IC50 from 18.2 to 196.6 mu mol.L-1 and 9.2 to 196.2 mu mol.L-1, respectively. Importantly, based on the substitution pattern, it is possible to modulate selectivity against AChE or BuChE and some derivatives also produced a balanced inhibition. In general, the most promising analogues were N-alkyl (C-2-C-6) carbamates and isomers with a changed position of phenolic hydroxyl. N-[3,5-Bis(trrfluoromethyl)phenyl]-3-bromo-5-hydroxybenzamide 4a was the best inhibitor of both cholinesterases. Conclusion: A wide range of the derivatives improved the activity of the bit 1, they were superior to carbamate drug rivastigmine against AChE and some of them also against BuChE. The most promising derivatives also fit physicochemical space and structural features for CNS drugs together with an escalated lipophilicity.
N- [3,5-Bis (trifluormethyl) fenyl] -5-brom-2-hydroxybenzamid Analogy: Nové inhibitory acetyl- a butyrylcholinesterázy
Keywords: acetylcholinesterase; benzamides; butyrylcholinesterase; carbamates; enzyme inhibition; salicylanilides; thiocarbamates; acetylcholinesteráza; benzamidy; butyrylcholinesteráza; karbamáty; inhibice enzymů; salicylanilidy; thiokarbamáty